Design of a frequency selective rasorber with fast roll‐off and wide absorption/transmission band. Issue 10 (13th July 2021) - Jia, Yuxin; Ma, Chang; Zhai, HuiQing; Liu, ChangYuan
Abstract: A frequency selective rasorber (FSR) with fast roll‐off and wide absorption/transmission band is introduced in this article, working as a band‐pass filter from 1.7 to 3.1 GHz, while working as an absorber from 5.72 to 17 GHz. The proposed FSR is designed by the lossy layer at the top and the band‐pass frequency selective surface (FSS) at the bottom. The lossy layer is constructed by two parts including a square loop and a series RLC structures to provide a wide absorption band. The band‐pass FSS is a three‐tier structure including two patch layers and one meander line layer in the middle. This multilayer FSS is used to generate a transmission window in S band and a wide reflection band in the high frequency. The working mechanism of the FSR is explained by the equivalent circuit model. Finally, the fabricated prototype and the measurement results are presented to verify the design of the FSR.